Policies that Address Sustainable Building Practices - Marisa Romero; Mark E. Hostetler (EDIS)
Circular 1518, a 12-page document by Marisa Romero and Mark E. Hostetler, compiles and summarizes seven city and county ordinances that promote sustainable buildings. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, May 2007.